Measurement of heat release during hydration and carbonation of ash disposed in landfills using an isothermal calorimeter. (1st April 2021) - Narode, Asmita; Pour-Ghaz, M.; Ducoste, Joel J.; Barlaz, Morton A.
Highlights: Hydration and carbonation of Ca-containing ash contributes to heat in landfills. Developed method to measure heat of hydration and carbonation in a calorimeter. Recovered 79–90% of hydration heat; 65–75% of carbonation heat using pure materials. Similar results with water and synthetic leachate. Abstract: Temperatures as high as 100 °C have been reported at a few municipal solid waste (MSW) landfills in the U.S. A recently published model describing landfill heat accumulation identified reactions that contribute significant heat to landfills including the hydration and carbonation of Ca-containing wastes such as ash from MSW and coal combustion. The objective of this study was to develop a method to measure heat release from Ca-containing ash by isothermal calorimetry. The method was confirmed by comparing measured heat release from hydration and carbonation of pure CaO and Ca(OH)2 to the theoretical heat. Theoretical heat release was determined by characterizing test materials before and after experiments using thermogravimetric analysis (TGA) and X-ray diffraction (XRD). Heat recovery efficiencies with both water and synthetic leachate ranged from 79 to 90% for CaO hydration and between 65 and 74% for Ca(OH)2 carbonation, with no effect attributable to leachate. Additionally, simultaneous hydration and carbonation of CaO/Ca(OH)2 mixtures resulted in efficiencies of 65 to 74%. The developed method was applied to eight samples that were excavated from a landfill and known to contain coal ash, and the ratio of measured to theoretical heat was 0.5 to 4. Thus, calculation of theoretical heat release from XRD data was not a good predictor of the experimentally measured heat release. The developed method can be used by landfill operators to evaluate the heat potential of a waste, thereby facilitating decisions on the quantity of a waste that can be buried in consideration of landfill temperatures.